Transformation of educational philosophy: an evaluation of higher education management innovation against the background of Big Data - Zichen Xu; Shi Cheng (Trans/Form/Ação, 2024)
With the modern information society’s rapid development, Big Data (BD) has brought great convenience to residents’ lives. Under the background of BD, the application of information technology in various fields has become a trend. Through the transformation of educational philosophy, Higher Education Management (HEM) has also taken on new characteristics and generated new development directions. This article explored the shortcomings and reasons of traditional HEM work, pointed out current problems in it and explained the necessity of innovation in it. This article also analyzed the advantages and development of BD technology in management work. Through the new ideas, methods and tools brought by Big Data technology to Higher Education Management, it was demonstrated that BD technology supported the development of innovative teaching mode, provided a positive learning environment and reduces management costs. Based on the characteristics of HEM work and the advantages of BD technology, innovative research was conducted to analyze students’ learning efficiency and enthusiasm to illustrate the innovative effect of HEM work. BD technology, including Artificial Intelligence and precise and flexible management, brings new ideas, methods and tools to HEM, effectively improving efficiency, enhancing students’ happiness and reducing labor management costs. They support the development of innovative teaching models, offer university students a positive learning environment and cut down on management costs.